The Role of Self-Management Techniques for Reducing Gadget Addiction: Empowering Students Toward Healthier Digital Habit - Widyastuti, Dian Ari; Putri, Lucky Resta Widias (citeus, 2025)
This study aims to examine the effectiveness of individual counseling using self-management techniques in reducing gadget addiction among students. The research employed an experimental approach with a single-subject design (SSD). One participant, a student from Yogyakarta, Indonesia was selected through purposive sampling. Data were collected using observation guidelines and a gadget addiction scale. Data analysis in single-subject research emphasizes individual data, and therefore, this study utilized visual analysis through graphical representations. The results of the visual analysis indicated a reduction in gadget addiction, as demonstrated by the A-B-A design graph. Based on these findings, it can be concluded that individual counseling incorporating self-management techniques is effective in decreasing gadget addiction in students. The outcomes of this study may serve as a valuable reference for guidance and counseling practitioners in implementing self-management-based individual counseling interventions to address gadget addiction among students.